Depression, Hopelessness, and Complicated Grief in Survivors of Suicide - Bellini, Samantha; Erbuto, Denise; Andriessen, Karl; Milelli, Mariantonietta; Innamorati, Marco; Lester, David; Sampogna, Gaia; Fiorillo, Andrea; Pompili, Maurizio (Frontiers in Psychology, 2018)
Suicide often has a severe impact on the surviving family and friends. There is a need to better understand the psychological and psychopathological consequences of losing a loved one by suicide. To assess hopelessness, depression, suicide risk, complicated grief, intrusive memories and avoidance in a sample of suicide survivors. In this observational study, thirty-five bereaved individuals were recruited at the Suicide Prevention Centre of Sant'Andrea Hospital in Rome. Subjects were administered a series of validated instruments: Beck Depression Inventory II (BDI), the Beck Hopelessness Scale (BHS), the Inventory of Complicated Grief (ICG), the Impact of Event Scale (IES), the Subjective Happiness Scale (SHS), and the Satisfaction With Life Scale (SWLS). Most survivors (62.8%) obtained high scores on measures of complicated grief. Scores on the measure of complicated grief were associated with intrusiveness of thoughts and memories, attempts to prevent the thoughts and emotions related to the event, depressive symptoms and hopelessness, lower scores for feelings of happiness and satisfaction with life. A subgroup of suicide survivors may be at risk of severe psychological distress and suicidal behavior. Identification of these survivors is a necessary step for providing appropriate counseling and psychotherapy.